Sametingsvalget 2021 - Bergh, Johannes; Berg-Nordlie, Mikkel; Falch, Torvald; Gaup, Sara Ellen; Haugom Nordfjell, Laila; Selle, Per; Saglie, Jo; Stein, Jonas; Strømsnes, Kristin (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2025)
The 2021 Sami Parliament Election: A Changing Party System? explores Sami parliamentary politics in Norway, in particular, events relating to the 2021 election, as well as long-term trends in Sami politics. The data is based on voter surveys that have been conducted during every Sami parliamentary election since 2009 and additional sources, such as informant interviews.